Metal Complexes with Dicyclohexanone/Disalicylidene Carbohydrazone - Jha, R.R.; (Mishra) Jha, U. (Asian Journal of Chemistry, 2012)
Metal(II) complexes of the type [M2(DCHC)2(H2O)4]X2 and [M2(DSC)2] where M = Co2+, Ni2+, Zn2+, Cd2+ and Hg2+, DCHC = dicyclohexanone carbohydrazone and DSC = disalicylidene carbohydrazone and X = Cl–, Br– and NO3–, have been isolated in neutral medium. All the complexes except of Zn2+, Cd2+, and Hg2+ are paramagnetic. The complexes with DCHC have octahedral stereochemistry and complexes with that of DSC except copper have tetrahedral stereochemistry around the metal ions.